The Role Of Destination Image As An Intervening Variable In The Influence Of Tourism Events And Social Media On Revisit Intention At Sorake Beach, South Nias Regency - Yupiter Mendrofa (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the influence of tourism events and social media on tourists’ revisit intention, with destination image serving as an intervening variable at Sorake Beach, South Nias Regency. A quantitative research approach was employed using a survey method involving 150 tourists who had previously visited Sorake Beach. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that tourism events and social media have a positive and significant effect on destination image and revisit intention. Furthermore, destination image is found to have a positive and significant influence on tourists’ revisit intention. Mediation analysis reveals that destination image significantly mediates the relationship between tourism events, social media, and revisit intention. These findings highlight that the formation of a positive destination image is a key mechanism in encouraging tourists’ intention to revisit. This study contributes theoretically to the development of tourist behavior models based on destination image and provides practical implications for destination managers in designing tourism event strategies and social media marketing oriented toward sustainable tourism.